Analisis Penerapan Sak Etap Pada Badan Usaha Milik Desa (BUMDESA) Napoleon Desa Waitii Barat Kecamatan Tomia Kabupaten Wakatobi - Sumantri, Sri; Salihi, Said Saleh; Ayudin, Ayudin (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze the implementation of SAK ETAP in Napoleon Village-Owned Enterprises (BUMDesa), West Waitii Village, Tomia District, Wakatobi Regency. The data analysis method used in this research is descriptive qualitative. Data sources were obtained from primary data by direct interviews with West Waitii Village officials, Tomia District, Wakatobi Regency, especially the village head, village secretary and village treasurer, as well as secondary data obtained from Napoleon Village-Owned Enterprise (BUMDesa) documents, West Waitii Village, Tomia District, Wakatobi Regency. . The research results show that BUMDesa Napoleon West Waitii Village in Tomia District has prepared financial reports but has not implemented SAK ETAP. This is caused by the limited knowledge of BUMDesa managers regarding accounting. The suggestion for this is that the West Waitii Village Government, Tomia District, Wakatobi Regency should provide training/coaching to BUMDesa Managers regarding preparing financial reports and creating accounting applications for BUMDesa to make it easier for managers to apply accounting, so that BUMDesa managers can make reports in accordance with Financial Accounting Standards. (SAK) ETAP